Drowning in Muddied Waters or Swimming Downstream?: A Critical Analysis of Literature Reviewing in a Phenomenological Study through an Exploration of the Lifeworld, Reflexivity and Role of the Researcher - Fry, Jane M. (The Indo-Pacific journal of phenomenology, 2017)
This paper proceeds from examining the debate regarding the question of whether a systematic literature review should be undertaken within a qualitative research study to focusing specifically on the role of a literature review in a phenomenological study. Along with pointing to the pertinence of orienting to, articulating and delineating the phenomenon within a review of the literature, the paper presents an appropriate approach for this purpose. How a review of the existing literature should locate the focal phenomenon within a given context is illustrated by excerpts from the first author's literature review within a descriptive phenomenological study. Also discussed is the important issue of when the researcher should fully enter the attitude of the phenomenological reduction and how this may influence the study.